REHABILITATION OF CHILDREN WITH CEREBRAL PALSY - Suyarova Kamola Abdurashidovna; Norbekov Bobur Sharif o'g'li; Nurulloev Suhrobjon Zoyit o'g'li; Mahmadiyorova Firuza Muzaffar Qizi; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
Infantile cerebral palsy (ICP) is a concept that unites a group of motor disorders resulting from damage to various brain structures in the perinatal period. Cerebral palsy can include mono-, hemi-, para-, tetra-paralysis and paresis, pathological changes in muscle tone, hyperkinesis, speech disorders, shaky gait, movement coordination disorders, frequent falls, lagging of the child in motor and mental development. In cerebral palsy, there may be intellectual impairment, mental disorders, epilepsy, hearing and visual impairment. Diagnosed cerebral palsy is diagnosed mainly by clinical and anamnestic data. The algorithm of examination of a child with cerebral palsy is aimed at identifying concomitant pathology and excluding other congenital or postnatal pathology. People who have cerebral palsy should undergo rehabilitation therapy for life, receive medical, surgical and physiotherapeutic treatment as needed.
Keywords: status epilepticus; sinocapal status; neurology